北極圏における融雪時期の解析 ～アラスカ観測より～ - 中村, 文彬; 榎本, 浩之; 茂手木, 勇紀; ヌアスムグリ, アリマス; 金, 籠元; 舘山, 一孝; Fumiaki, Nakamura; Hiroyuki, Enomoto; Yuki, Motegi; Alimasi, Nuerasimuguli; Kim, Yongwon; Kazutaka, Tateyama (2010)
第33回極域気水圏シンポジウム ポスター発表 conference object